Social Investment by Union-Based Pension Funds and Labour-Sponsored Investment Funds in Canada - Quarter, Jack; Carmichael, Isla; Sousa, Jorge; Elgie, Susan (Relations industrielles / Industrial Relations, 2001)
SummaryThis study has two objectives: first, to understand the extent of social investment among union-based pension funds as well as labour-sponsored investment funds in Canada; second, to understand the factors that affect social investment strategies among such funds. A national sample of 189 pension funds with assets of at least $50 million was drawn from the Canadian Pension Fund Investment Directory (Toronto: Maclean Hunter). The sample also included 10 labour-sponsored investment funds, half the number of such funds in Canada. The data indicate that pension funds in Canada have minimal social investment. There is somewhat higher social investment among labour-sponsored investment funds, and particularly labour-sponsored investment funds with genuine union sponsorship. The study also explored factors related to social investment by funds.